Understanding Regime Shifts in Social-Ecological Systems Using Data on Direct Ecosystem Service Use - Censkowsky, Philipp; Otto, Ilona M. (Frontiers in Environmental Science, 2021)
This paper takes a new look on transition processes in social-ecological systems, identified based on household use of direct ecosystem services in a case study in KwaZulu-Natal, South Africa. It builds on the assumption that high dependence on local ecosystems for basic needs satisfaction corresponds to a “green loop” type of system, with direct feedbacks between environmental degradation and human well-being. Increasing use of distant ecosystems marks a regime shift and with that, the transition to “red loops” in which feedbacks between environmental degradation and human well-being are only indirect. These systems are characterized by a fundamentally different set of sustainability problems as well as distinct human-nature connections. Through the analysis of a case study in KwaZulu-Natal, South Africa, the paper contributes to existing research that has so far only identified and mapped social-ecological systems with cross-sectional data. The results show that direct ecosystem service use is inherently dynamic and associated with socio-economic and political change, underpinning the relevance of transdisciplinary research. The proposed theoretical concept and methodology can be applied to other contexts to study variegated human-nature relationships in the context of transformative change.